The effect of powder properties on laser powder bed fusion of tungsten carbide-cobalt - Govender, Preyin (Stellenbosch : Stellenbosch University, 2025)
Govender, P. 2025. The Effect of Powder Properties on Laser Powder Bed Fusion of Tungsten Carbide-Cobalt. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/9035c506-2d63-494e-88ba-4130103facd8